Quirky the remarkable story of the traits, foibles, and genius of breakthrough innovators who changed the world - Schilling, Melissa A. (PublicAffairs, 2018)
What makes some people so spectacularly innovative, producing triumph after triumph, often in fields in which they had no specialized training?